PENERAPAN SISTEM JAJAR LEGOWO TERHADAP PENINGKATAN PRODUKTIFITAS DAN NILAI TAMBAH PADI SAWAH - Bharoto, Bharoto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
The purpose of this research is to know the difference of productivity and value added Legowo row planting system on a regular row planting system (tiles) of paddy. Research sites in the region, namely Prambanan subdistrict and village Sumberharjo Madurejo. Samples were taken by purposive many as 30 farmers. Implementation of the project participants Movement Integrated Plant Management (GPTT) The data is taken directly interviewing farmers using questioner. The results showed that with Legowo row planting system 4: 1, increase the productivity of rice 10.38%, and value-added (B / C ratio) 5.7 More than one row planting system legowa means better or more profitable than the systems of row planting regular (tiles). when viewed from the analysis of feasibility, O / i ratio and ROI, sisitem Legowo row planting system is higher than the tiles are Legowo row planting system O / I ratio of 2.8 and cropping systems tiles O / I ratio of 2.7 and ROI, the system legowo row planting 186% and 172.4% tiles cropping systems